Cost effective weed management approach under SRI cultivation - Anitha, S (Indian Farming, 2015)
In situ cultivation of dhaincha and subsequent incorporation of dhaincha by desiccating it at 30 days after sowing by spraying 2, 4 – D @ 1 kg/ha is a cost effective weed management alternative for rice under SRI management. By growing dhaincha there was a significant reduction in weed count (74%) and weed dry matter production (64%) and thereby a saving of labour requirement by 44 man days and labour cost by 3750/ha for weeding alone. It is very effective in supplying the required quantity of organic manures (12 tonnes/ha) to rice with minimum investment i.e. the cost of dhaincha seeds and its sowing charges alone without any yield reduction of rice.